POTRET KEMISKINAN PEMULUNG DI PERKOTAAN KOTA PEKANBARU (STUDI KASUS TPA MUARA FAJAR) - Azani Pinkan; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
As happened in other metropolitan cities in Indonesia, it turns out that there are still residents of Pekanbaru city who only have a low level of education and income level, including the scavenger community who are usually scattered in the outskirts of Pekanbaru city and many who live in the area. less livable. One of the areas inhabited by the scavenger community in the city of Pekanbaru with residential conditions that are less suitable for habitation is the residential area in the Muara Fajar final disposal area. This study on the life of scavengers began with a concern over the lives of scavengers in general living in slum areas. But they can still survive with all the opportunities and obstacles that exist. Scavenger jobs are not the main choice, but limited education and skills make some people want to do this kind of work. The purpose of this study is to determine the poverty portrait of urban scavengers in Pekanbaru City and to find out the socio-economic life of scavengers in Pekanbaru City. The methods used are descriptive and qualitative methods; The informants in this study were the Muara Fajar TPA supervisor, local RT and scavengers. Data collection techniques are interviews, observation and documentation. This study concludes that the portrait of the poverty of scavengers in Pekanbaru City is people who work as scavengers whose economic conditions are weak, which makes them scavengers. The socio-economic life of scavengers is never separated from every collection of used goods and garbage that contains selling value, which is then quoted back by each scavenger. Thus the life of scavengers can be well directed even though their economic income is below the poverty line on a daily basis. Keywords: Portrait, Poverty, Scavengers